The Influence of Motivation, Perceived Discrimination, Acculturation Strategies, and Adaptation on Destination Loyalty - Jamaludin, Nor Lelawati; Farradina, Syarifah; Wee, Nur Melissa binti Mohammad Faisal; Sadik, Mohd Zaki Bin; Jamil, Norina Ahmad; Mahpar, Nurul Salizawatee; Sani, Nur Zania Azurin Abdullah; Sani, Nur Zania Azurin Abdullah (Advances in Social Sciences Research Journal, 2024)
Destination loyalty in education tourism can be characterized by tourists’ intention to revisit and their recommendations of the place to others, serving as primary indicators. However, even though there is growing interest among academia and industry players in the concept of destination loyalty, our comprehension of the psychological factors influencing destination loyalty intention remains inadequate. Existing literature has not yet addressed the topic of education tourism in Norway. Therefore, this research explores the attributes of destination loyalty and the influence of perceived discrimination, acculturation strategies, psychological and sociocultural adaptation in elucidating international students' intention to exhibit loyalty in Norway. The theoretical framework draws on motivation theory (Crompton, 1979), acculturation theory (Berry, 1990; Berry, 1997), adaptation (Searle & Ward, 1990), and loyalty theory (Backman & Crompton, 1991), which have been adapted to include perceived discrimination as an additional exploratory variable. This study extends previous research on destination loyalty by investigating the impact of acculturation strategies on enhancing the relationship between travel-related attributes and loyalty. The study utilizes partial least squares (PLS) to examine the links between the variables. Based on a questionnaire survey of international students in Norway, the findings indicate that psychological adaptation and acculturation strategies have a positive impact on loyalty. The coefficient of determination (R2) reveals that the final structural model can account for 34% of the variance in international students’ loyalty behavior. These results highlight the importance for stakeholders in the education tourism industry to recognize the influence of acculturation strategies and psychological adaptation on travel loyalty. Understanding these factors can contribute to enhancing destination competitiveness in education tourism and ensuring its long-term sustainability. The study concludes by acknowledging its limitations and encouraging further research in this area.